Midterm outcomes of fenestrated TEVAR using physician-modified endovascular grafts for zone 2. (June 2022) - Bi, Jiaxue; Niu, Fang; Li, Peng; Dai, Xiangchen; Zhu, Jiechang; Liu, Zongwei
Objectives: To summarize the experience and midterm outcomes of physician-modified endovascular grafts for zone 2 thoracic endovascular aortic repair. Methods: A retrospective analysis was conducted of 51 consecutive patients (mean age 57.6 ± 12.5 years, 39 males) treated with thoracic endovascular aortic repair using physician-modified endovascular grafts for reconstructing the left subclavian artery from November 2015 to December 2019. The primary endpoints during follow-up were the overall mortality, aorta-related mortality, and major complications. The secondary endpoints were reintervention and the patency of the target branches, the demographics and technical details were also described and analyzed. Results: Sixty-three thoracic stent-grafts were deployed in 51 patients and emergency surgery was performed in 10 patients (19.6%). Technical success was 94.1% (48/51). The incidence of perioperative complications was 15.7%, and the 30-day mortality was 0%. At a mean follow-up of 42.0 ± 14.4 months (range, 14–63 months), all the left subclavian arteries remained patent. All-cause mortality was 3.9% (2/51) and not aorta-related deaths. Estimated survival at one and three years was 98.0 ± 1.9% and 96.0 ± 2.8%, respectively. Conclusions: The physician-modified endovascular grafts is feasible and effective to preserve left subclavian artery in thoracic endovascular aortic repair for aortic arch pathologies with unhealthy proximal landing zone.